The Effectiveness of Virtual Reality in Introducing Places of Worship to Young Children - Miranda, Dian; Perdina, Siska; Lukmanulhakim, Lukmanulhakim; Novitasari, Desy; Utami, Nadia Maharani (STAI Auliaurrasyidin Tembilahan, 2025)
This study evaluates the effectiveness of Virtual Reality (VR) in introducing places of worship to young children. The research focuses on three key aspects: children's engagement with the VR media, their conceptual understanding as measured by Student Worksheets (LKPD), and teacher responses to its implementation. Data were gathered via direct observation, teacher questionnaires, and analysis of completed student worksheets. The findings reveal that VR significantly enhances student engagement through its interactive and immersive nature. The realistic visual experience provided by VR also facilitated a better understanding of the concepts compared to conventional methods. Teachers reported that the VR technology was user-friendly, time-efficient, and required no complex technical skills. In conclusion, this study confirms that VR is an effective tool for introducing places of worship to young children, showing significant potential to improve the quality of future learning experiences.